Drug-Related Problems of Children With Chronic Diseases in a Chinese Primary Health Care Institution: A Cross-Sectional Study - Ni, Xiao-Feng; Yang, Chun-Song; Zeng, Li-Nan; Li, Hai-Long; Diao, Sha; Li, De-Yuan; Wu, Jin; Liu, Yuan-Chun; Jia, Zhi-Jun; Cheng, Guo; Zhang, Ling-Li (Frontiers in Pharmacology, 2022)
Introduction: The condition of drug-related problems (DRPs) might be severe for children with chronic diseases in primary heath care institutions, but there is a lack of relevant researches. Objective: In this cross-sectional study, we intended to explore the incidence, types, causes and influencing factors of DRPs in this specific group. Methods: We recruited children with chronic diseases who visited the pediatric outpatient department in a primary heath care institution from July 1 to October 12, 2021. Clinical pharmacists identified manifest or potential DRPs through medication therapy reviews. Results: A total of 188 children with chronic diseases were included, and 584 DRPs were identified in 89.89% participants. The most common type of DRPs was treatment effectiveness (83.56%), of which 67.29% were potential DRPs; the second common type was treatment safety (14.21%), of which 89.16% were potential DRPs. The most common cause of DRPs was concentrated in the process of use (42.24%), such as “patient uses/takes less drug than prescribed or does not take the drug at all”, “patient stores drug inappropriately”, “patient administers/uses the drug in a wrong way”; the second common cause was in the process of dispensing (29.83%), such as “necessary information not provided or incorrect advice provided” , “prescribed drug not available”; the third common cause was in the process of prescribing (26.21%), such as “drug dose too low” , “no or incomplete drug treatment in spite of existing indication”. The number of combined medicines was a influencing factor for the number of DRPs (P<0.05). Conclusion: This cross-sectional study showed the condition of DRPs among children with chronic diseases in the primary heath care institution was serious. In the future, pharmacists should consider to formulate pharmaceutical intervention strategies for this specific group according to their characteristics of DRPs.